2016
DOI: 10.1007/s11103-016-0523-2
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of soybean gene Fg1 encoding flavonol 3-O-glucoside/galactoside (1→6) glucosyltransferase

Abstract: Flavonoids are important secondary metabolites in plants. Sugar-sugar glycosyltransferases are involved in the final step of flavonoid biosynthesis and contribute to the structural diversity of flavonoids. This manuscript describes the first cloning of a sugar-sugar glucosyltransferase gene in the UGT family that attaches glucose to the 6″-position of sugar bound to a flavonol. The results provide a glimpse on the possible evolution of sugar-sugar glycosyltransferase genes and identify putative amino acids res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…Several flavonoid 3-O-(6″-O-rhamnosyl) glycosides, such as rutin, quercetin 3-O-robinobioside [34], and kaempferol 3-O-rutinoside [35] have been found in buckwheat plants, and we detected rutin and a compound predicted to be quercetin 3-O-robinobioside in the common buckwheat cultivar Shinano No.1 used in this study ( Figure S7); these compounds are likely to be produced by FeF3G6″RhaT. The enzymatic property of FeF3G6″RhaT is similar to that of 6″-Orhamnosyltransferase from Glycine max (GmF3G6″ RT) [17], which showed 52% identity with FeF3G6″ RhaT. In contrast, 6″-O-rhamnosyltransferases from Citrus (Cs1,6RhaT and Cm1,6RhaT), which shared 57% identity with FeF3G6″RhaT, reacted with flavonoid 7-O-glucosides as major substrates and reacted with flavonol 3-O-glucosides as minor substrates [12].…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Several flavonoid 3-O-(6″-O-rhamnosyl) glycosides, such as rutin, quercetin 3-O-robinobioside [34], and kaempferol 3-O-rutinoside [35] have been found in buckwheat plants, and we detected rutin and a compound predicted to be quercetin 3-O-robinobioside in the common buckwheat cultivar Shinano No.1 used in this study ( Figure S7); these compounds are likely to be produced by FeF3G6″RhaT. The enzymatic property of FeF3G6″RhaT is similar to that of 6″-Orhamnosyltransferase from Glycine max (GmF3G6″ RT) [17], which showed 52% identity with FeF3G6″ RhaT. In contrast, 6″-O-rhamnosyltransferases from Citrus (Cs1,6RhaT and Cm1,6RhaT), which shared 57% identity with FeF3G6″RhaT, reacted with flavonoid 7-O-glucosides as major substrates and reacted with flavonol 3-O-glucosides as minor substrates [12].…”
Section: Discussionsupporting
confidence: 62%
“…At present, some members of rhamnosyltransferases, which catalyze rhamnosylation of the sugar moiety of flavonoid glycosides, have been characterized. These include flavanone 7-O-glucoside 6″-O-rhamnosyltransferase from Citrus sinensis and C. maxima [12,13], flavanone 7-O-glucoside 2″-O-rhamnosyltransferase from C. maxima [14], anthocyanidin-3-O-glucoside 6″-O-rhamnosyltransferase from Petunia x hybrida [15] and Lobelia erinus [16], and flavonoid 3-O-glucoside 6″-O-rhamnosyltransferase from Glycine max [17].…”
mentioning
confidence: 99%
“…The key isoflavonoid gene GmIFS (Jung et al, 2000) was also downregulated in GmMYB176-OE. No known glycosyltransferase (Dhaubhadel et al, 2008; Di et al, 2015; Rojas Rodas et al, 2016) were found differentially expressed in GmMYB176-OE or GmMYB176-Si compared to control.…”
Section: Discussionmentioning
confidence: 90%
“…On the other hand, kaempferol/quercetin 3- O -glucosyl(1 → 2)glucoside derivatives were identified in petals and leaves of the Petunia cultivar ‘Mitchell’ (Bloor et al 1998 ; Davies et al 1998 ) and petals of P. × hybrida clone RL01 (Griesbach 1993 ). Flavonol 3- O -glucoside: 2″- O -glucosyltransferase/6″- O -glucosyltransferase also recognizes flavonoid 3- O -galactoside as a sugar acceptor at a comparable level (Yonekura-Sakakibara et al 2014 ; Di et al 2015 ; Rodas et al 2016 ). These data suggest that the target gene encoding flavonol 3- O -galactoside: 2″- O -glucosyltransferase may be expressed in tissues other than pollen and may be involved in the 2″- O -glucosylation of flavonol 3- O -glucosides.…”
Section: Resultsmentioning
confidence: 99%